Women's experience of abortion in Aotearoa/New Zealand : conflicts and contradictions in choice : a thesis presented in partial fulfilment for the requirement for the degree of Master of Arts in Psychology at Massey University, Manawatu, New Zealand - Cooper, Dayna (Massey University, 2014)
"No woman wants an abortion like she wants an ice cream cone or a Porsche. She wants an abortion like an animal caught in a trap wants to gnaw off its own leg." — Anonymous Contemporary constructions of abortion in New Zealand have limited abortion rhetoric to a distinct binary of prochoice or prolife discourse. These binaries restrict the positions available to women when negotiating their experiences of abortion, and position women in a polarising discourse that does not sufficiently encompass the complexity of women’s lived experience of abortion. Limiting abortion rhetoric to the dominant binary has consequences for the creation and maintenance of abortion stigma, particularly internalised stigma, which can have negative consequences on women’s experience. This research aimed to examine the gap that psychological research has failed to explore by addressing the question of the effects of wider sociocultural factors in women’s experience of abortion and the discourses that they engaged with to construct their narratives. Five women who had terminated a pregnancy before 20 weeks gestation were interviewed about their abortion experience in New Zealand using one to one conversational interviews. A feminist poststructuralist discourse analysis was conducted, attending to the binary that enabled and limited positions for women to occupy in regards to the wider sociocultural forces regulating abortion. The analysis showed that the binary both created and exacerbated women’s struggle and confusion in their decision-making with the inflexibility of positions on either side of abortion rhetoric. It explored how women position themselves as ‘both/and’ within the binary rather than ‘either/or’ and identified some of the conflicts this creates. Further alternative discourses of maternity, individualism and female sexuality textured the prochoice and prolife abortion rhetoric and enabled an examination of how other discourses regulating women’s bodies are salient in women’s talk about their abortions. This research provides an understanding of the effects of dominant abortion discourses and the power relations implicit in them on women’s construction of their experience. Furthermore, how these discourses may be resisted and implications for policy going forward are also examined to reduce stigma and silence surrounding abortion for women in New Zealand and improve the social conditions in which women access this procedure.